Techonososiopreneur: Development Strategy of Halal Travel Agency (Using VCIT Model) - Amaliyah Amaliyah; Muhammad Iqbal Arrasyid; Aam Bastaman; Dwi Sunu Kanto (International Journal of Supply Chain Management, 2020)
The potential of Halal Travel Agents business is increasing by considering the increasing position of Indonesia as a country that is the second largest Muslim tourist destination in 2018. Even the Indonesian government in 2019 targets the first rank as a country that becomes a Muslim tourist. In addition, related to the industrial revolution, the process has led to industry 4.0, so that in addition to referring to people's demands for Muslim travel services that are getting better, Halal Travel Agencies also need to carry out various evaluations and developments to run amid the ongoing 4.0 industrial revolution. This type of research is qualitative using a phenomenological with analytical techniques that refer to the VCIT model (Value, Innovation, Culture, Technology). The research results obtained are change the corporate mindset of the first travel agency, there must be more intensive and assertive promotion, education and details about Halal Travel Menu